Polymyalgia Rheumatica Post-SARS-CoV-2 Infection - Carolina Duarte-Salazar; José Eugenio Vazquez-Meraz; Lucio Ventura-Ríos; Cristina Hernández-Díaz; José Arellano-Galindo (Case Reports in Immunology)
There is growing evidence that infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can lead to dysregulation of the immune system and, consequently, the development of autoimmune phenomena. Here, we describe the case of a 75-year-old woman with rheumatic manifestations characterized by intense musculoskeletal pain and stiffness in the neck and shoulders, with sudden onset and with the inability to raise her arms. The patient was admitted with severe pain located in the neck and shoulders. Previously, she had oropharyngeal pain, severe fatigue, and fever; a real-time polymerase chain reaction test for COVID-19 was positive. Two weeks later, the patient presented localized musculoskeletal pain in the neck and shoulders. Relevant laboratory results included an erythrocyte sedimentation rate of 46 mm/hr and a negative rheumatoid factor test; ultrasound findings with bilateral subacromial–subdeltoid bursitis were observed. A diagnosis of polymyalgia rheumatica (PMR) was initially made according to the EULAR/ACR provisional classification criteria for PMR; however, due to C-reactive protein negativity, the diagnosis was established based on symptoms. Management was with prednisone at the dose of 25 mg/day for 4 weeks and progressive reduction until prednisone suspension. The patient showed complete recovery at 6 months of follow-up. In this case, COVID-19 was implicated in the development of autoimmune and inflammatory rheumatic manifestations. PMR is a rare rheumatic condition that should be included in the wide range of rheumatologic manifestations expressed post-SARS-CoV-2 infection.